Vitamin A Deficiency in the Early-Life Periods Alters a Diversity of the Colonic Mucosal Microbiota in Rats - Chen, Baolin; Liu, Shu; Feng, Di; Xiao, Lu; Yang, Ting; Li, Tingyu; Sun, Wuqing; Chen, Jie (Frontiers in Nutrition, 2020)
Vitamin A deficiency (VAD) remains a public health issue worldwide, affecting pregnant women and children. The early-life microbiota is a potentially effective intervention target for modulating immune and metabolic development of the host. This paper investigates the effects of VAD during different life periods on the structure of the colonic mucosa microbiota in adolescent rats. The results showed that the concentrations of serum retinol were greater than approximately 1.05 µmol/L in maternal VA normal (VAN)rats and less than 0.7 µmol/L in maternal VAD rats, while the serum retinol levels were higher than 0.7 µmol/L in the pups of the VAN group and below 0.5 µmol/L in the pups of the VAD group. Compared to the offspring persistent with VAN from embryonic stage (group A), all the remaining groups exhibited an increased ratio of Firmicutes/Bacteroidetes abundance. A metagenome analysis (LEfSe) and a differentially abundant features approach using Metastats for genus abundances revealed that Diaphorobacter and Psychrobacter were increased in the offspring persistent with VAD from embryonic stage (group B);Bifidobacterium was decreased and Staphylococcus was increased in the offspring with VAD after weaning (group C); Propionibacterium and Enterobacter were increased significantly in the offspring with VAD during gestation(group E); and Ochrobactrum was increased in group B and the offspring with VAD during gestation and lactation(group D). Faecalibacterium abundance was significantly and positively related to serum retinol levels, while that of Staphylococcus was significantly and negatively correlated with serum retinol levels. VAD in different life periods can alter the gut microbiome in rats, but VAD in the early-life periods (especially gestation and/or lactation) leads to a diversity of the colonic mucosal microbiota in adolescent rats as well as an imbalance of the ratio between Firmicutes and Bacteroidetes. The early-life period may become a time window of VA intervention to improve intestinal microbiota caused by VA deficiency, but the specific mechanism requires more in-depth research.